Provision of NHS generalist and specialist services to care homes in England: review of surveys - Iliffe, Steve; Davies, Susan L.; Gordon, Adam L.; Schneider, Justine; Dening, Tom; Bowman, Clive; Gage, Heather; Martin, Finbarr C.; Gladman, John R.F.; Victor, Christina; Meyer, Julienne; Goodman, Claire (Cambridge University Press, 2016)
Background: The number of beds in care homes (with and without nurses) in the United Kingdom is three times greater than the number of beds in National Health Service (NHS) hospitals. Care homes are predominantly owned by a range of commercial, not-for-profit or charitable providers and their residents have high levels of disability, frailty and co-morbidity. NHS support for care home residents is very variable, and it is unclear what models of clinical support work and are cost-effective. Objectives: To critically evaluate how the NHS works with care homes.MethodsA review of surveys of NHS services provided to care homes that had been completed since 2008. It included published national surveys, local surveys commissioned by Primary Care organisations, studies from charities and academic centres, grey literature identified across the nine government regions, and information from care home, primary care and other research networks. Data extraction captured forms of NHS service provision for care homes in England in terms of frequency, location, focus and purpose. Results: Five surveys focused primarily on general practitioner services, and 10 on specialist services to care home. Working relationships between the NHS and care homes lack structure and purpose and have generally evolved locally. There are wide variations in provision of both generalist and specialist healthcare services to care homes. Larger care home chains may take a systematic approach to both organising access to NHS generalist and specialist services, and to supplementing gaps with in-house provision. Access to dental care for care home residents appears to be particularly deficient. Conclusions:Historical differences in innovation and provision of NHS services, the complexities of collaborating across different sectors (private and public, health and social care, general and mental health), and variable levels of organisation of care homes, all lead to persistent and embedded inequity in the distribution of NHS resources to this population. Clinical commissioners seeking to improve the quality of care of care home residents need to consider how best to provide fair access to health care for older people living in a care home, and to establish a specification for service delivery to this vulnerable population.